2003
DOI: 10.1007/s00228-003-0627-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ketoconazole on venlafaxine plasma concentrations in extensive and poor metabolisers of debrisoquine

Abstract: Ketoconazole consistently affected the disposition of venlafaxine in EMs of debrisoquine while the response in PMs was erratic. The precise mechanisms underlying this interaction remain to be elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 11 publications
1
28
0
Order By: Relevance
“…Similarly, studies have been conducted in extensive versus poor metabolizers of CYP2D6 and the extent of drug-drug interactions was compared. These studies have consistently reported a greater degree of inhibition of wild-type CYP2D6 enzyme compared with variant forms of CYP2D6 (Hamelin et al, 2000;Lessard et al, 2001;LLerena et al, 2001;Lindh et al, 2003). The variant alleles of CYP2C19, as well as those of CYP2D6, in the above studies cause either a splicing defect or a frame shift resulting in either premature termination of translation or a truncated protein.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Similarly, studies have been conducted in extensive versus poor metabolizers of CYP2D6 and the extent of drug-drug interactions was compared. These studies have consistently reported a greater degree of inhibition of wild-type CYP2D6 enzyme compared with variant forms of CYP2D6 (Hamelin et al, 2000;Lessard et al, 2001;LLerena et al, 2001;Lindh et al, 2003). The variant alleles of CYP2C19, as well as those of CYP2D6, in the above studies cause either a splicing defect or a frame shift resulting in either premature termination of translation or a truncated protein.…”
Section: Discussionmentioning
confidence: 81%
“…However, genetic polymorphisms in drug-metabolizing enzymes are not routinely evaluated for their impact on drug interactions during clinical studies. Genotype-dependent inhibition has been demonstrated with CYP2D6 and CYP2C19 genetic polymorphisms (Hamelin et al, 2000;Lessard et al, 2001;LLerena et al, 2001;Lindh et al, 2003; Yasui-Furukori et al, 2004a,b;Uno et al, 2006), but these polymorphisms resulted in expression of inactive proteins that should not be subject to inhibition. No clinical studies have explored the effect of single nucleotide polymorphisms (SNPs) resulting in reduced activity enzymes (e.g., CYP2C9*3) and their effect on the degree of inhibition interactions observed.…”
Section: Introductionmentioning
confidence: 99%
“…For example, fluoxetine is primarily metabolized via N-demethylation by CYP2D6, 2C9, and 3A (von Moltke et al, 1997;Margolis et al, 2000), paroxetine by demethylenation of its methylenedioxy group by CYP2D6 (Bloomer et al, 1992), venlafaxine by O-demethylation by CYP2D6 (Otton et al, 1996;Fogelman et al, 1999), and citalopram by CYP3A4-, 2D6-, and 2C19-catalyzed N-demethylation (Kobayashi et al, 1997;von Moltke et al, 1999von Moltke et al, , 2001Olesen and Linnet, 1999). As such, these drugs have been shown to be subject to drug interactions by various inhibitors of cytochrome P450 enzymes such as quinidine and ketoconazole (Lessard et al, 1999;Eap et al, 2003;Lindh et al, 2003). Also, some of these agents have been shown to exhibit substantial differences in pharmacokinetics in subjects who lack CYP2D6 or CYP2C19, such as fluoxetine, paroxetine, and venlafaxine (Hamelin et al, 1996;Lessard et al, 1999;Liu et al, 2001;Charlier et al, 2003;Lindh et al, 2003;Yu et al, 2003).…”
mentioning
confidence: 99%
“…As such, these drugs have been shown to be subject to drug interactions by various inhibitors of cytochrome P450 enzymes such as quinidine and ketoconazole (Lessard et al, 1999;Eap et al, 2003;Lindh et al, 2003). Also, some of these agents have been shown to exhibit substantial differences in pharmacokinetics in subjects who lack CYP2D6 or CYP2C19, such as fluoxetine, paroxetine, and venlafaxine (Hamelin et al, 1996;Lessard et al, 1999;Liu et al, 2001;Charlier et al, 2003;Lindh et al, 2003;Yu et al, 2003).…”
mentioning
confidence: 99%
“…Recently, Lindh et al (2003) carried out an interesting clinical investigation to evaluate the role of CYP3A4 inhibition on the disposition of venlafaxine in EMs (n = 14) and PMs (n = 7) of CYP2D6 isozyme. The exposure (AUC) ratio of O-desmethylvenlafaxine to venlfaxine was well correlated with the debrisoquine metabolic ratio, suggesting a clear role of CYP2D6 isozyme in the pharmacokinetic disposition of venlafaxine.…”
Section: Venlafaxinementioning
confidence: 99%